Revealing underlying mechanisms affecting electrokinetic remediation of an artificially Cu- and Pb-contaminated loess using the external regulatory system with adsorbent - Hu, Wenle; Cheng, Wen-Chieh; Wen, Shaojie; Kang, Nongbo (Frontiers in Materials, 2022)
Given extensive mining-metallurgical activities in the North-West of China, handling copper- and lead-rich wastewater is deemed to be a challenging task. Inappropriate handling of the copper- and lead-rich wastewater can cause an accumulation of copper and lead in surrounding environments, leading to serious threats to human health. Electrokinetic (EK) technology is an increasingly popular alternative to traditional approaches for contaminated soil remediation because of its high effectiveness and low risk of secondary pollution. This study first proposed the external regulatory system with the adsorbent (ERSA) and investigated the effect of electrode type, ERSA, and cation exchange membrane (CEM) on the EK remediation of an artificially Cu- and Pb-contaminated loess. An EK reactor that incorporates the ERSA was applied to the EK experiments to circulate the electrolyte, not only making pH surrounding the cathode lower but preventing the formation of precipitation. The electrokinetic geosynthetics (EKG) electrode released H+ and OH- faster and promoted its migration towards the specimen. However, due to the faster precipitation near the cathode, the increase in remediation efficiency was hindered. Further, considering the use of the ERSA, the decrease of soil pH near the cathode reduced the precipitation, thereby enhancing the EK remediation efficiency. On the other hand, the use of CEM lowered the soil pH, increased the soil electrical conductivity (EC) and electric current, and aggravated the electroosmotic flow (EOF). The Cu remediation efficiency using the modified EK reactor was largely lifted up to 85.52%, while the Pb remediation efficiency to 75.51%. These results shed light on an enhancement on the EK remediation efficiency and the potential of applying the modified EK reactor to remedying the copper- and lead-rich water bodies.